Islamic Family Law in Tunisia: Reforms, Characteristics, and Challenges - Mala Hayati; Rahma Zulkhairi Yati; Aulil Amri; Putri Azizah; Henri Bimawan; Inayatul Fitri (An-Nisa: Journal of Islamic Family Law, 2025)
Tunisia is a country in North Africa with a Muslim majority population that underwent significant reforms in family law after independence in 1956 through the passage of the Code du Statute Personnel (CSP). The reform is known to be progressive because it promotes gender equality and the protection of women's rights, while remaining grounded in Islamic values. Previous studies have focused more on normative aspects or described Tunisia as a model for family law reform in the Islamic world, but there is still limited research that explores the characteristics of this reform in a socio-political context, especially after the 2011 Revolution. This study uses a literature review method with a descriptive-qualitative approach to analyze regulations related to marriage, divorce, marital rights and obligations, and inheritance in Tunisian family law. The results of the study show that the reform of family law in Tunisia is marked by a balance between the principles of modernity and religious tradition, which is reflected in egalitarian policies towards women and restrictions on discriminatory practices in the family. These findings affirm Tunisia's position as a pioneer of Islamic family law reform with a distinctive model, while revealing the dynamics and challenges that arose in its implementation after the 2011 Revolution. This research provides an academic contribution in the form of a critical analysis of the Tunisian experience which can be an important reference for the development of Islamic family law in other Muslim countries.